Modeling the Multidimensional Predictors of Multisite Musculoskeletal Pain Across Adulthood-A Generalized Estimating Equations Approach - Ville-Heikki Ahlholm; Ville-Heikki Ahlholm; Viljami Rönkkö; Viljami Rönkkö; Leena Ala-Mursula; Jaro Karppinen; Jaro Karppinen; Jaro Karppinen; Petteri Oura; Petteri Oura; Petteri Oura (Frontiers Media S.A., 2021)
Background: Multisite pain is commonly chronic and often lacks its initial role as a potential tissue damage signal. Chronic pain among working-age individuals is a risk for disability and imposes a major burden on health care systems and society. As effective treatments for chronic pain are largely lacking, better identification of the factors associated with pain over working years is needed.Methods: Members of the Northern Finland Birth Cohort 1966 participated in data collection at the ages of 31 (n = 4,028) and 46 (n = 3,429). Using these two time points, we performed a multivariable analysis of the association of socioeconomic, occupational, psychological and lifestyle factors (i.e., low education, living alone, low household income, unemployment, occupational physical exposures [hard physical labor, leaning forward, back twisting, constant moving, lifting loads of ≥ 1 kg], physical inactivity, regular smoking, regular drinking, overweight, and psychiatric symptoms) with the number of musculoskeletal pain sites (i.e., upper extremity, lower extremity, lower back, and the neck-shoulder region; totalling 0-4 pain sites). The data were analyzed using generalized estimating equations.Results: At the age of 31, multisite pain was reported by 72.5% of men and 78.6% of women. At the age of 46, the prevalence of multisite pain was 75.7% among men and 82.7% among women. Among men, the number of pain sites was positively associated with age (rate ratio 1.05, 95% confidence interval 1.01-1.08), low household income (1.05, 1.01-1.08), unemployment (1.13, 1.06-1.19), any occupational exposure (1.17, 1.12-1.22), regular smoking (1.06, 1.02-1.11), and psychiatric symptoms (1.21, 1.17-1.26). Among women, the number of pain sites was positively associated with age (1.06, 1.04-1.10), unemployment (1.10, 1.05-1.15), any occupational exposure (1.10, 1.06-1.13), regular smoking (1.06, 1.02-1.10), overweight (1.08, 1.05-1.11), and psychiatric symptoms (1.19, 1.15-1.22); living alone was negatively associated with the number of pain sites (0.95, 0.91-0.99).Conclusion: Of the studied predictors, psychiatric symptoms, occupational physical exposures and unemployment were most strongly associated with multisite pain among both sexes. The results of this study deepen the understanding of the underlying factors of and comorbidities behind multisite pain, and help develop pain relief and rehabilitation strategies for working-age individuals with multisite pain.